The International Criminal Court and the Lord's Resistance Army leaders: prosecution or amnesty? - Ssenyonjo, Manisuli (Netherlands International Law Review, 2007)
On 13 October 2005, the International Criminal Court (ICC) Pre-Trial Chamber II unsealed the warrants of arrest for five senior leaders of the Lord's Resistance Army/Movement (LRA/M) for crimes against humanity and war crimes committed in Uganda since July 2002. While these warrants were yet to be executed, the Ugandan government entered negotiations with the LRA/M rebels. As a result Uganda's President Yoweri Museveni, disregarding the ICC arrest warrants, announced a ‘total amnesty’ for the LRA combatants in July 2006 on the condition that the rebels renounced terrorism and accepted peace. Following the amnesty offer, an agreement on cessation of hostilities between the Ugandan government and the LRA/M was concluded with effect from 29 August 2006. This article considers the question whether a ‘total amnesty’ to individuals indicted by the ICC may be binding upon the ICC.
Keywords: International Criminal Court, amnesty, crimes against humanity, war crimes, Lord's Resistance Army